Challenges Faced by Small and Medium Enterprises in Raising Finance in Uganda - Turyahikayo, Everest (International Journal of Public Administration and Management Research (IJPAMR), 2015)
The purpose of this paper was to discuss challenges faced by SMEs in raising finance in Uganda. Basing on the critical document review, the paper uses social capital theory to demonstrate that Ugandan SMEs continue to face challenges in raising finance. Such challenges include inadequate collateral to secure loans; information opaqueness; low level technical and management skills; lack of professionalism; competition; inability to afford long term financing among others. The paper suggests various ways in which these challenges can be addressed. Such suggestions include; developing social capital through networks; SME friendly policy framework; proper information management; and improvement of management skills. Alternative sources of finance available to SMEs include; investment into capital markets, long term financing, leasing and franchising. The paper concludes that SMEs should put emphasis on the development of social networks as a mechanism to develop financing opportunities.